In Search of Fatima: A Palestinian Story - Karmi, Ghada (London Verso)
Ghada Karmi’s acclaimed memoir relates her childhood in Palestine, flight to Britain after the catastrophe, and coming of age in Golders Green, the north London Jewish suburb. A powerful biographical story, In Search of Fatima reflects the author’s personal experiences of displacement and loss against a backdrop of the major political events which have shaped conflict in the Middle East. Speaking for the millions of displaced people worldwide who have lived suspended between their old and new countries, fitting into neither, this is an intimate, nuanced exploration of the subtler privations of psychological displacement and loss of identity
Hardcover
Pictures
Keywords: Karmi, Ghada; Physicians - Palestine - Bibliography; Women, Palestinian Arab - Bibliography; Israel - Arab war, 1948-1949 - Jerusalem - Personal narratives, Palestinian Arab